Oxytocin and Vasopressin Involved in Restraint Water-Immersion Stress Mediated by Oxytocin Receptor and Vasopressin 1b Receptor in Rat Brain - Zhao, Dong-Qin; Ai, Hong-Bin (PLOS ONE, 2011)
Aims Vasopressin (AVP) and oxytocin (OT) are considered to be related to gastric functions and the regulation of stress response. The present study was to study the role of vasopressinergic and oxytocinergic neurons during the restraint water-immersion stress. Methods Ten male Wistar rats were divided into two groups, control and RWIS for 1h. The brain sections were treated with a dual immunohistochemistry of Fos and oxytocin (OT) or vasopressin (AVP) or OT receptor or AVP 1b receptor (V1bR). Results (1) Fos-immunoreactive (Fos-IR) neurons dramatically increased in the hypothalamic paraventricular nucleus (PVN), the supraoptic nucleus (SON), the neucleus of solitary tract (NTS) and motor nucleus of the vagus (DMV) in the RWIS rats; (2) OT-immunoreactive (OT-IR) neurons were mainly observed in the medial magnocellular part of the PVN and the dorsal portion of the SON, while AVP-immunoreactive (AVP-IR) neurons mainly distributed in the magnocellular part of the PVN and the ventral portion of the SON. In the RWIS rats, Fos-IR neurons were indentified in 31% of OT-IR neurons and 40% of AVP-IR neurons in the PVN, while in the SON it represented 28%, 53% respectively; (3) V1bR-IR and OTR-IR neurons occupied all portions of the NTS and DMV. In the RWIS rats, more than 10% of OTR-IR and V1bR-IR neurons were activated in the DMV, while lower ratio in the NTS. Conclusion RWIS activates both oxytocinergic and vasopressinergic neurons in the PVN and SON, which may project to the NTS or DMV mediating the activity of the neurons by OTR and V1bR.